Archaeomegalomus gen. nov.: A remarkable new brown lacewing from mid-Cretaceous Kachin amber from northern Myanmar (Neuroptera: Hemerobiidae) - Nakamine, Hiroshi; Yamamoto, Shûhei; Takahashi, Yui (Zootaxa, 2022)
A new fossil species of Hemerobiidae, Archaeomegalomus burmiticus gen. et sp. nov., is described from mid-Cretaceous Kachin amber of northern Myanmar. This new genus is the third Mesozoic Hemerobiidae with a single stem of the radius posterior (RP) in the forewing. This suggests that A. burmiticus is one of the specialized side branches within the basal Hemerobiidae. Our study sheds more light on the Cretaceous diversity of Mesozoic brown lacewings, suggesting potentially higher generic and species paleodiversity of the hemerobiids in Burmese amber.